2014
DOI: 10.1186/1556-276x-9-111
|View full text |Cite
|
Sign up to set email alerts
|

Field emission properties and growth mechanism of In2O3 nanostructures

Abstract: Four kinds of nanostructures, nanoneedles, nanohooks, nanorods, and nanotowers of In2O3, have been grown by the vapor transport process with Au catalysts or without any catalysts. The morphology and structure of the prepared nanostructures are determined on the basis of field emission scanning electron microscopy (FESEM), x-ray diffraction (XRD), and transmission electron microscopy (TEM). The growth direction of the In2O3 nanoneedles is along the [001], and those of the other three nanostructures are along th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 36 publications
(41 reference statements)
1
16
0
Order By: Relevance
“…2 have been displayed in our previous work which is about the field emission properties of the In 2 O 3 nanostructures [7]. The highly magnified FESEM image of the synthesized In 2 O 3 nanotowers is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…2 have been displayed in our previous work which is about the field emission properties of the In 2 O 3 nanostructures [7]. The highly magnified FESEM image of the synthesized In 2 O 3 nanotowers is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2e recorded with an electron beam perpendicular to the surface of the In 2 O 3 nanotower demonstrates that the In 2 O 3 nanotower is single crystal and the growth direction is along [200].
Fig. 2 a The highly magnified FESEM image and b the XRD pattern of the In 2 O 3 nanotowers [7]. c The bright-field image, d the HRTEM image, and e the SAED pattern of an individual In 2 O 3 nanotower [7]
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As for the growth mechanisms of these In 2 O 3 microcrystals and In 2 O 3 micro‐rods, careful observation revealed that a particle‐like shape was not found on the top of the structures as it would be in the case of VLS process often reported as the growth mechanism on Au‐catalyzed In 2 O 3 1D‐structures . Therefore, the growth mechanism associated with our structures cannot be explained by the well‐known VLS mechanism.…”
Section: Resultsmentioning
confidence: 71%